(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This research aims to define the nature of international crimes and the jurisdiction of the International Criminal Court. It also reviews the assassination of journalist Shireen Abu Akleh, its investigations, and local and international responses to the assassination. It also aims to draw lessons learned from the case of Shireen Abu Akleh regarding the protection of journalists in conflict zones and the strengthening of international accountability mechanisms. The research followed a descriptive and analytical approach, collecting information and data related to the case of Shireen Abu Akleh and the international legal framework for crimes against journalists. This information was critically analyzed to draw conclusions and present recommendations. The research reached several conclusions, the most important of which is that the establishment of the International Criminal Court represents an important step in establishing a permanent international criminal justice system. However, the mere existence of the court is not sufficient to ensure international justice. Continued efforts are required from the international community to implement the principles and provisions of this system, by strengthening international cooperation in the field of investigations and extradition of accused persons, providing the necessary logistical and financial support for the court’s work, and expanding the scope of states’ accession to the Rome Statute to ensure the comprehensiveness of the court’s jurisdiction. The study emphasizes that the role of the International Criminal Court complements, rather than replaces, the efforts of states to investigate and establish the facts. This complementary principle enhances the effectiveness of the international justice system, as it encourages states to assume their responsibilities in investigating international crimes and prosecuting their perpetrators. In the case of Shireen Abu Akleh, we see the importance of this complementarity, as national and international investigations can complement each other to provide a more comprehensive picture of what happened. However, the unwillingness of some states to conduct comprehensive and independent investigations highlights the importance of an international mechanism capable of intervening when necessary. This balance between national and international efforts is essential to ensuring justice and protecting the rights of victims.